2011
DOI: 10.1007/s10342-011-0533-1
|View full text |Cite
|
Sign up to set email alerts
|

Do harrowing and fertilisation at middle rotation improve tree growth and site quality in Eucalyptus globulus Labill. plantations in Mediterranean conditions?

Abstract: Effects of harrowing and fertilisation on tree growth, understory vegetation, forest floor litter and soil properties were studied in a field experiment installed in a 5-year-old first rotation eucalypt plantation. The treatments were harrowing (H), fertilisation (F), harrowing and fertilisation (HF) and a control without any treatments (C), with four replicates. Tree growth, root mass, tree nutrition status, understory vegetation, mass of forest floor litter and soil physical and chemical properties were moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…These authors tested different combinations of NPK in southeast Spain and found that tree growth in sandy soils (fertilizer application in a five-year-old E. globulus plantation) was significantly enhanced by addition of N. In soils over slates (fertilizer application in a seven-year-old E. globulus plantation), the trees responded to fertilization with N and K [68]. However, these proposals are controversial, as different results were obtained in fertilization trial in five-year-old E. globulus plantation in central Portugal, where Madeira et al [69] reported no positive response to fertilizer application for a cutting cycle of 14 years. The authors suggest that fertilizer application may be useful for enhancing soil quality and ensuring the long-term sustainability of eucalyptus plantations.…”
Section: Maintenance Fertilizationmentioning
confidence: 98%
“…These authors tested different combinations of NPK in southeast Spain and found that tree growth in sandy soils (fertilizer application in a five-year-old E. globulus plantation) was significantly enhanced by addition of N. In soils over slates (fertilizer application in a seven-year-old E. globulus plantation), the trees responded to fertilization with N and K [68]. However, these proposals are controversial, as different results were obtained in fertilization trial in five-year-old E. globulus plantation in central Portugal, where Madeira et al [69] reported no positive response to fertilizer application for a cutting cycle of 14 years. The authors suggest that fertilizer application may be useful for enhancing soil quality and ensuring the long-term sustainability of eucalyptus plantations.…”
Section: Maintenance Fertilizationmentioning
confidence: 98%